Les enjeux organisationnels de la reprise du travail de salariés après une longue absence - Célia Quériaud; Bernard Dugué; Johann Petit (Perspectives Interdisciplinaires sur le Travail et la Santé)
This study is based on an ergonomic intervention conducted at the request of a bank due to difficulties encountered by employees who were returning to work after a long-term absence. Though many studies have been conducted about return-to-work following a health problem (accident or illness), the particular aim of this study was to identify the key factors needed to facilitate return-to-work whatever the reason for the absence. The study analysis focused on 16 cases of return-to-work after an absence of more than three months.We decided to consider return-to-work as a process beginning before the moment of the absence and continuing after the moment when the employee returned to the workplace. This allowed us to widen the possibilities of action all throughout this process. We identified three main categories of absence and return-to-work. We likewise emphasized the need for an organizational management of return-to-work which should involve a few key actors, namely : the occupational health doctor, immediate supervisors, Human Resources service, and workers’ representatives.